Optical Character Recognition Applications in Libraries - Chacón Alvarado, Lucía (1989)
The sophisticated technology of optical characters has reached great popularity in libraries because his versatility allows to turn material printed or typed by Computational means without need to rig the information. His future and application in the libraries is very promising because it provides solutions to administrative problems and facilitates the technical process of the information.